Unveiling The Impact of Illegal Online Loans on Cashless Lifestyles And Digital Marketing: A Case Study of Students At Bengkalis State Polytechnic's Language Department - Putra, Halim Dwi; Sabri, M.; Malik, A. (Politeknik Negeri Bengkalis, 2024)
This study explores the repercussions of illegal online loans on cashless lifestyles and digital marketing amongstudents at the Language Department of Bengkalis State Polytechnic. The primary objective is to analyze how theseunregulated financial activities influence students' financial behaviors and their interaction with digital marketing.Employing a mixed-methods research design, the study integrates quantitative surveys and qualitative interviews to capturea broad spectrum of impacts. The quantitative component involved administering structured questionnaires to 10 students,selected through stratified random sampling to ensure diverse representation across academic levels and disciplines. Thequalitative aspect comprised semi-structured interviews with 10 students who had direct or indirect experiences with illegalloans, providing deeper insight into the personal and psychological effects of their financial decisions. The findings reveala significant trend towards increased use of cashless payment methods among students entangled with illegal loans,primarily due to the ease of transaction it offers for loan disbursement and repayment. Moreover, there was a noticeableuptick in students' exposure to aggressive digital marketing campaigns, which often exploit their financial vulnerabilities.Despite these conveniences, the study also uncovered substantial adverse effects, including heightened financial stress andconcerns over data privacy, with over 60% of respondents reporting increased anxiety and intrusive advertising. Theresearch underscores the dual-edged nature of illegal online loans in shaping financial and digital engagement, highlightingthe need for comprehensive regulatory frameworks and consumer education to protect vulnerable populations in the digitalage